1998
DOI: 10.1046/j.1460-9568.1998.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a contribution of lateral inhibition to orientation tuning and direction selectivity in cat visual cortex: reversible inactivation of functionally characterized sites combined with neuroanatomical tracing techniques

Abstract: We have previously reported that cells in cat areas 17 and 18 can show increases in response to non-optimal orientations or directions, commensurate with a loss of inhibition, during inactivation of laterally remote, visuotopically corresponding sites by iontophoresis of gamma-aminobutyric acid (GABA). We now present anatomical evidence for inhibitory projections from inactivation sites to recording sites where 'disinhibitory' effects were elicited. We made microinjections of [3H]-nipecotic acid, which selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 101 publications
11
99
0
1
Order By: Relevance
“…Our data confirm previous results demonstrating that inhibition is an important contributor to directional tuning (3,7,9). It has previously been thought that most of MT's input is highly direction selective (12,13,26).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our data confirm previous results demonstrating that inhibition is an important contributor to directional tuning (3,7,9). It has previously been thought that most of MT's input is highly direction selective (12,13,26).…”
Section: Resultssupporting
confidence: 92%
“…We tested this possibility by reducing local inhibition within MT. Inhibition substantially contributes to the generation of direction selectivity in V1 (3,4,(6)(7)(8)(9). We hypothesized that MT direction selectivity should be largely unaffected by removal͞reduction of inhibition, if inherited from earlier areas, whereas direction selectivity should be substantially reduced if generated de novo within MT.…”
Section: Contribution Of Inhibitory Mechanisms To Direction Selectivimentioning
confidence: 99%
See 1 more Smart Citation
“…In the model, blockade of inhibition from neurons with a specific orientation preference should cause neighboring prediction neurons to show increased response to that orientation, rather than simply causing a general disinhibition to all orientations. Such effects have been recorded in V1 (Crook et al, 1998), and analogous data have been obtained from cortical area TE (Wang et al, 2000). The current model is also consistent with neurophysiological evidence that the strength of lateral inhibition peaks for stimuli presented at the preferred orientation of the recorded cortical cell (Ferster, 1986;Sato et al, 1996;Sompolinsky and Shapley, 1997).…”
supporting
confidence: 88%
“…Much of the evidence that has been put forth in support of recurrent models of orientation tuning comes from experiments not restricted to layer IV simple cells. For instance, it has been demonstrated that remote inactivation of orthogonal orientation columns can reduce the orientation selectivity of neurons located 350-700 lm distant [13,15]. This provides strong support for the importance of an intact cortical network for normal orientation tuning.…”
Section: Generation Vs Maintenance Of Tuningmentioning
confidence: 87%